Manajemen Mutu Lembaga Pendidikan Berprestasi Pada Madrasah Ibtidaiyah - Sri Setyo; Mudhofir Mudhofir; Siti Choiriyah (Jurnal Ilmiah Ekonomi Islam, 2021)
This study aims to determine the quality management of outstanding educational institutions at Madrasah Ibtidaiyah, where this research is conducted at Madrasah Ibtidaiyah Negeri 6 Sukoharjo. This research was conducted on quality planning at Madrasah Ibtidaiyah Negeri (MIN) 6 Sukoharjo in realizing outstanding educational institutions, reviewing and describing in more depth the implementation of quality at Madrasah Ibtidaiyah Negeri (MIN) 6 Sukoharjo in realizing educational institutions with achievement, and assessing and describing in depth more in-depth about evaluating the quality at Madrasah Ibtidaiyah Negeri (MIN) 6 Sukoharjo in realizing outstanding educational institutions. The methodology in this study uses a qualitative approach. Data collection techniques in this study are by observation, interviews and documentation. The method used to check the validity of the data is method triangulation, namely by using various methods as a consideration. The results showed that: 1). Planning: establishing the vision and mission as quality guidelines, commitment to the implementation of national standard schools, a comfortable and good service process, increasing the quality of students' input, using quality references set by the government, quality planning in management reviews, improving the quality of inputs in Madrasah Ibtidaiyah Negeri (MIN) 6 Sukoharjo is the result of a sustainable program, improving services through the distribution of questionnaires, the existence of a quality assurance design or design at Madrasah Ibtidaiyah Negeri (MIN) 6 Sukoharjo as a line and reference in order to maintain and improve educational institutions with achievement. 2). Implementation: implementing a national standard curriculum and a typical school curriculum, educators and education personnel have a minimum qualification of a bachelor, there is satisfaction from students and parents / guardians of students as users, graduates are 100% and equipped with expertise, the presence of representative infrastructure, transparent education management, very good and very close relations between the school and the community, the existence of special services for supporting learning activities. 3). Evaluation: conducting self-evaluation of school performance based on accountability, transparency, efficiency and effectiveness, evaluating the learning process at the end of each semester, compiling reports from the results of self-evaluations that have been carried out, compiling priority scales of various activities and follow-up programs on the results of self-evaluation the results of the analysis as a construction of improvements carried out gradually and continuously in realizing outstanding educational institutions.